Optimization of Virtual Reality-Based Flood Simulation by Manipulating Particle System - David Fahmi Abdillah; Achmad Basuki; Tri Harsono (Institute of Computer Science (IOCS), 2022)
VR (Virtual reality) is a technology that is gaining in popularity and many fields have used it in the applications they have developed. VR is the best tool to use as a learning medium and simulations that previously could not be done due to a lack of qualified technology, such as natural disaster simulations where users can feel like one of the victims who are affected by natural disasters and can feel it directly through simulations. the. However, this technology can also have side effects when using it, such as discomfort, dizziness to nausea. This is commonly known as cybersickness. To reduce the possibility of cybersickness, it is necessary to optimize the application by keeping the frame rate at least more than 60-90 fps. Particles are one of the systems that can affect the performance frame rate if not optimized by manipulating their emission for each system. This paper will explain how to optimize VR applications and analyze experiments involving FPS optimization in VR applications.